Emissões de gases do efeito estufa em sistemas multitróficos de aquicultura - Assunção, Marcelo Henrique Correa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The aim of this study was to investigate Greenhouse Gases (GHG) fluxes in aquaculture ponds. We tested if the use of Integrated Multi Trophic Aquaculture (IMTA) with Yellow tail tetra (Astyanax lacustris) and Amazon River prawn (Macrobrachium amazonicum) in a tropical environment changes the GHG flows in comparation with A. lacustris monoculture. We developed an experiment in earthen ponds with three treatments and four replications: monoculture (Tetra), two species free in the pond (Free IMTA) and fishes in cage and prawns free (Cage IMTA). Experiment ran 68 days between November and January 2016. We measured fluxes of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) with diffusive and dissolved methodologies. Mean of diffusive fluxes was -8.93 mg.m-2 .h-1 for CO2, -0.88 mg.m-2 .h-1 for CH4 e 1.78 mg.m-2 .h-1 for N2O. Concentration of CO2 oscillated between 0.0481 and 0.6668 mg.L-1 , CH4: 0.0003 and 0.0053 mg.L-1 e N2O: 0.0789 a 0.1177 mg.L-1 . Our results indicate variations over time, with higher fluxes at the beginning of experiment, decreasing over the growing period and trend of neutrality regarding to the GHG emissions at the end of experimental period.

O objetivo deste estudo foi investigar o fluxo de gases do efeito estufa (GEE) em viveiros de criação de organismos aquáticos. Nós testamos se o uso de sistemas multitróficos e multiespaciais (IMTA), povoados com lambari-do-rabo-amarelo (Astyanax lacustris) e camarão-da-amazônia (Macrobrachium amazonicum) numa região tropical, altera o fluxo de gases do efeito estufa em comparação com um sistema de monocultivo de A. lacustris. Nós desenvolvemos um experimento em viveiros de fundo natural com três tratamentos e quatro réplicas: monocultivo (Tetra), IMTA livre (Free IMTA) e IMTA tanque rede (Cage IMTA). O experimento durou 68 dias, entre os meses de novembro e janeiro de 2016. Nós mensuramos os fluxos de dióxido de carbono (CO2), metano (CH4) e óxido nitroso (N2O) por meio das metodologias difusiva e dissolvida. A média dos fluxos na metodologia difusiva foi de -8.93 mg.m-2.h-1 para o CO2, -0.88 mg.m-2.h-1 para o CH4 e 1.78 mg.m-2.h-1 para o N2O. A concentração de CO2 variou de 0.0481 a 0.6668 mg.L-1, CH4 de 0.0003 a 0.0053 mg.L-1 e N2O de 0.0789 a 0.1177 mg.L-1. Nossos resultados indicam variação ao longo do tempo, com maior fluxo de GEE no início do experimento, diminuição ao longo do período de cultivo e tendência de neutralidade com relação a emissão de GEE no final do período experimental.
Greenhouse gas emissions in multitrophic systems of aquaculture
Keywords: Greenhouse effect; Sustainability; Efeito estufa; Sustentabilidade; Astyanax; IMTA